2022
DOI: 10.1242/dev.200510
|View full text |Cite
|
Sign up to set email alerts
|

BRAVO self-confined expression through WOX5 in the Arabidopsis root stem-cell niche

Abstract: In animals and plants, stem-cell niches are local microenvironments that are tightly regulated to preserve their unique identity while communicating with adjacent cells that will give rise to specialized cell types. In the primary root of Arabidopsis thaliana, two transcription factors, BRAVO and WOX5, among others, are expressed in the stem-cell niche. Intriguingly, BRAVO, a repressor of quiescent center divisions, confines its own gene expression to the stem-cell niche, as evidenced in a bravo mutant backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Recent work has shown that besides transcriptional regulation, these transcription factors also form protein complexes that localise to nuclear bodies in the columella stem cells, which could serve an important role in CSC fate determination (Burkart et al, 2022 ). Besides PLT, WOX5 expression is also dependent on the BRASSINOSTEROIDS AT VASCULAR AND ORGANIZING CENTER R2R3- MYB transcription factor (BRAVO), which has been suggested to act through the formation of a hetero dimer complex and through subsequent disruption of the WOX5 negative feedback on itself (Betegón‐Putze et al, 2021 ; Mercadal et al, 2022 ). This, in turn, activates BRAVO expression, and as such, this mechanism confines the expression of these transcription factors to a small domain in the stem cell niche.…”
Section: Mobile Shr and Wox5mentioning
confidence: 99%
“…Recent work has shown that besides transcriptional regulation, these transcription factors also form protein complexes that localise to nuclear bodies in the columella stem cells, which could serve an important role in CSC fate determination (Burkart et al, 2022 ). Besides PLT, WOX5 expression is also dependent on the BRASSINOSTEROIDS AT VASCULAR AND ORGANIZING CENTER R2R3- MYB transcription factor (BRAVO), which has been suggested to act through the formation of a hetero dimer complex and through subsequent disruption of the WOX5 negative feedback on itself (Betegón‐Putze et al, 2021 ; Mercadal et al, 2022 ). This, in turn, activates BRAVO expression, and as such, this mechanism confines the expression of these transcription factors to a small domain in the stem cell niche.…”
Section: Mobile Shr and Wox5mentioning
confidence: 99%